Preference-Based Utility Scores for Adverse Events Associated With the Treatment of Gynecologic Cancers. Issue 6 (1st July 2013) - Jewell, Elizabeth L.; Smrtka, Michael; Broadwater, Gloria; Valea, Fidel; Davis, Debra M.; Nolte, Kimberly C.; Valea, Renea; Myers, Evan R.; Havrilesky, Laura J.
Abstract : Objective: Our goals were to (1) define a set of descriptive health states related to adverse events (AEs) associated with gynecologic cancer treatment with radical surgery and chemoradiation and (2) derive a set of quality of life–related utility scores corresponding to these health states. Methods: We developed a list of health states for grade 3/4 AEs related to gynecologic cancer treatment. Using the visual analog scale score and time trade-off (TTO) methods, valuation of each health state was obtained through interviews of 60 volunteers (15 cervical cancer survivors treated with surgery and/or chemoradiation and 45 women without a cancer diagnosis). Health states were ranked by mean/median TTO scores. Wilcoxon rank sum test was used to compare central tendencies related to patient and volunteer characteristics. Results: Patients and volunteers agreed on their preference rankings, with highest preference given to infection (median TTO = 1.0) and thrombosis (median TTO = 0.97). Lowest preference was assigned to radiation proctitis (median TTO = 0.87) and gastrointestinal fistula formation (median TTO = 0.83). Utility scores for the majority of health states were not significantly associated with age, race, parity, patient or volunteer status, history of abnormal Pap smear, stage of cervical cancer diagnosis, or personal experience of a serious treatment-related AE. Conclusions: This study helps establish preferences and quality-of-life utility scores for health states related to toxicities from surgery, radiation, and chemotherapy for gynecologic cancer treatment. Such information can be used to inform medical decision making/counseling and may be applied to future comparative effectiveness models in which radical surgery and/or chemoradiation are considered.